2014
DOI: 10.2105/ajph.2014.302239
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Network Social Capital on the Chances of Smoking Relapse: A Two-Year Follow-up Study of Urban-Dwelling Adults

Abstract: Social network capital reduced the chances of smoking relapse. Smoking cessation programs might aim to increase network diversity so as to prevent relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 27 publications
2
42
0
1
Order By: Relevance
“…Our findings are consistent with previous, mainly cross-sectional studies on the association between social networks and health risk behaviours [12,13,[15][16][17]20,[32][33][34]. Previous studies have shown, for example, that individuals who drink heavily report decreased levels of social activities, worse social anchorage and low contact frequency [32].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with previous, mainly cross-sectional studies on the association between social networks and health risk behaviours [12,13,[15][16][17]20,[32][33][34]. Previous studies have shown, for example, that individuals who drink heavily report decreased levels of social activities, worse social anchorage and low contact frequency [32].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown, for example, that individuals who drink heavily report decreased levels of social activities, worse social anchorage and low contact frequency [32]. Our results are also in line with those reporting a significant association between smoking and social isolation, low levels of social support, participation and network heterogeneity [33,34]. It has been suggested that for some people smoking provides a means of managing negative moods and stress that might result from having inadequate social relations [35].…”
Section: Discussionsupporting
confidence: 91%
“…A reduction between baseline and follow‐up in the number of smoking friends is also associated with quit attempts and success . Similarly, smokers living with fewer householders who smoke at baseline were more likely to successfully quit, although this was no longer apparent after 13 years in the longest study . However, these studies are based on whole population samples of smokers in high‐income countries with low smoking prevalence, rather than on samples from groups or countries with high smoking prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…Dois abordam a utilização da ARS na avaliação de serviços de saúde incluindo redes de controle 14,15 . Dos outros dezesseis artigos, oito tratavam de abordagens feitas com indivíduos [16][17][18][19][20][21][22][23] , cinco discutiam a questão sob a óptica de comunidades [24][25][26][27][28] e três abordavam questões dos serviços e sistemas de saúde 29,30 . Esses trabalhos buscaram investigar o efeito da rede social, do apoio social e do capital social, tanto em desfechos de ações em saúde 16,18,19,21,24,25 , quanto em programas de combate ao tabagismo 29,30 , controle da hanseníase 13 , em empresas 23 e comunidades religiosas 26 .…”
Section: Redes E Tabagismo: Breve Averiguação Bibliográficaunclassified